The child victims of the Aceh tsunami: stories of resilience, coping and moving on with life - Rahiem, Maila Dinia Husni; Krauss, Steven Eric; Rahim, Husni (Elsevier, 2018)
Disasters, regardless of the type or scale, have the potential to cause distress, or even severe distress. Children are usually the most affected by disaster, due to their physical, psychological and social vulnerabilities. Children are also the most vulnerable to face post- disaster challenges from psychological stress due to the limited availability of special care, protection and support. In this study, we explore the experiences of Acehnese children survivors of the 2004 tsunami. We set out to understand how these young people survived the tsunami, coped with the aftermath, and progressed with their lives following the tragedy. Our focus was on uncovering the multitude of trajectories, or pathways, that comprise the collective experiences of young people’s post-disaster lives. We employed a narrative, qualitative research approach, and conducted in-depth interviews with twenty-seven survivors. By giving a voice to their lives, we aimed to capture the successes and challenges that these young people face in attempting to live normal lives following a major disaster. At the time of the study, the participants had either lost one or both parents because of the tsunami. All of the respondents are now teenagers or young adults between the ages of 17 to 24 years old. The findings from the in-depth interviews revealed that all of the survivors have both shared and unique experiences. They all stated that in the immediate aftermath of the tsunami, they felt that there was a dearth of people to talk to and discuss their feelings. They also still feel the sadness, horror and trauma of the tsunami, yet they often keep their feelings to themselves. Lastly, they all accept the tragedy as their destiny from God. A variety of responses show differences in how they see their future. Some are very optimistic and still believe that they have a role in society, while others are confused, jobless and lost, to the extent that they feel uncertainty as to where their next meal will come from. The survivors also explained about the different types of support that they received immediately after the disaster including continuation support, long term support, and current support. How the young survivors coped with the immediate aftermath of the tsunami depended on the support received from their communities and the extent of their own inner strength and will to survive. Combined, these internal and external resources formed a personal resilience in surviving the tsunami, both in the short and long term. By studying the children of Aceh, aid workers, and support agencies -- especially those that work in the field of mental health/psychosocial programs -- can learn better ways to assist, help, and support children following natural disasters. Moreover, by understanding the children’s sources of resilience, we will be better informed about how families and schools should prepare and teach children, so that the victims are able to cope better with major disasters.